2018
DOI: 10.1016/j.omtm.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A Combined In Vivo HSC Transduction/Selection Approach Results in Efficient and Stable Gene Expression in Peripheral Blood Cells in Mice

Abstract: We recently reported on an in vivo hematopoietic stem cell (HSC) gene therapy approach. It involves the subcutaneous injections of G-CSF/AMD3100 to mobilize HSCs from the bone marrow into the peripheral blood stream and the intravenous injection of an integrating helper-dependent adenovirus vector system. HSCs transduced in the periphery homed back to the bone marrow, where they persisted long-term. However, high transgene marking rates found in primitive bone marrow HSCs were not reflected in peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 27 publications
6
47
0
Order By: Relevance
“…Viral gene therapy vectors specifically designed for NDD applications should be able to efficiently cross the blood-brain barrier (BBB), if delivered by iv infusion [44,49], and support an efficient transgene expression, regardless of aberrant cell signaling caused by the accumulation of toxic proteins or restoration of an autophagic state in neuronal cells [50]. For instance, vectors based on genomes of adeno-associated virus (AAV) [44,49,[51][52][53][54][55][56], lentivirus [57], type 1 herpes simplex virus [58], and Semliki Forest virus (SFV) [59] have been broadly used for neuron targeting. Extensive use of the above viruses in neuroscience is dictated by their natural ability to efficiently and selectively transduce and provide high transgene expression in neurons.…”
Section: Choosing An Ideal Vectormentioning
confidence: 99%
“…Viral gene therapy vectors specifically designed for NDD applications should be able to efficiently cross the blood-brain barrier (BBB), if delivered by iv infusion [44,49], and support an efficient transgene expression, regardless of aberrant cell signaling caused by the accumulation of toxic proteins or restoration of an autophagic state in neuronal cells [50]. For instance, vectors based on genomes of adeno-associated virus (AAV) [44,49,[51][52][53][54][55][56], lentivirus [57], type 1 herpes simplex virus [58], and Semliki Forest virus (SFV) [59] have been broadly used for neuron targeting. Extensive use of the above viruses in neuroscience is dictated by their natural ability to efficiently and selectively transduce and provide high transgene expression in neurons.…”
Section: Choosing An Ideal Vectormentioning
confidence: 99%
“…In our approach, the HSCs residing in the bone marrow niche were mobilized into the peripheral circulation through administration of granulocyte colonystimulating factor and the CXCR4 antagonist, Plerixafor/AMD3100. After in vivo transduction and selection with three low doses of O 6 -BG/ BCNU administered intraperitoneally with interval of 2 weeks, transgene marking in PBMCs was increased to > 50% [176]. HSPCs transduced in peripheral blood homed back to bone marrow shortly after transduction.…”
Section: In Vivo Hsc Transductionmentioning
confidence: 99%
“…This was likely in part due to a lack of a proliferative stimulus for the modified HSCs. To overcome this drawback, we therefore combined the in vivo transduction with an in vivo selection mechanism by incorporating a mutant O 6methylguanine-DNA methyltransferase (mgmt P140K ) gene that confers resistance to O 6 -BG/BCNU (O 6 -Benzylguanine/Carmustine) [176][177][178]. After in vivo transduction and selection with three low doses of O 6 -BG/ BCNU administered intraperitoneally with interval of 2 weeks, transgene marking in PBMCs was increased to > 50% [176].…”
Section: In Vivo Hsc Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential disadvantage is that the efficiency of gene manipulation was not as high as that typically seen in clinical trials using lentiviral vectors and ex vivo cell processing. Importantly, in a recent follow-up work it has been shown that a low-dose drug selection regimen provides gene-modified HSPCs that carry a O 6methylguanine-DNA methyltransferase (mgmt P140K ) transgene a selective survival and proliferation advantage, resulting in transgene expression in up to 80% of peripheral blood cells [82]. Taken together, we consider that Table 1 Estimated costs of GMP-grade viral versus non-viral gene transfer vectors per CAR-T cell product.…”
Section: Non-viral Engineering Of Hematopoietic Progenitor Cellsmentioning
confidence: 99%